(untitled) (Journal of Science and Technology, 2016)
Cassava and sweet potatoe pulps and starches have been fermented using a strain of Saccharomyces cerevisiae isolated from palm wine. Analysis of the fermented products indicated a high yield of ethanol. Comparative studies conducted using the isolated strain and a similar strain contained in Baker’s Yeast showed that the former is more efficient in fermenting blackstrap molasses than the latter.